Tranformasi Digital dan Efektivitas Pengendalian Internal Penagihan Service Charge Mengunakan Aplikasi MOaja - Cahyati, Diah Nur; Munandar, Agus (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The development of digital technology has encouraged organisations to transform their business processes and internal control systems. One form of this transformation is the digitisation of the service charge billing system in property management. This study aims to analyse the implementation of the MOaja application as a form of digital transformation and its impact on the effectiveness of internal control of service charge billing at the Grand Slipi Tower Building in West Jakarta using the COSO framework. The research method used is a descriptive qualitative approach through observation, interviews with management, and documentation studies of the billing system before and after the implementation of the MOaja application. The results of the study indicate that the implementation of the MOaja application has improved the efficiency and accuracy of the billing process, accelerated the delivery of information to tenants, and strengthened internal control, particularly in the areas of control activities, information and communication, and monitoring. The digitisation of the billing system also produced a clear audit trail, increased transparency, and minimised the risk of recording errors. Thus, digital transformation through the MOaja application not only improved the quality of service charge billing services but also contributed significantly to strengthening the effectiveness of internal controls in property management.